Structural Integrity Assessment of Genset Structure for Earthquake Loads - Vibhute, Avinash; Shinde, Vaibhav; Paranjape, Amar (International Journal of Computer Sciences and Engineering, 2019)
Structural integrity assessment is aspect of engineering which deals with the ability of a structure to support operating loads (such as weight, engine generated forces, etc.) without failure, and also includes the study of past structural failures in order to prevent failures in future designs. Integrity of a structure is the ability, to hold together as a single or group of structures, under various operating non-operating loads, including its own weight, without deforming excessively. Sometimes earthquake loads might be responsible for the structural failure of the Genset Structure. Primarily Genset is used as emergency power source but in some cases it needs to be used in rescue operations after earthquake events, so its structure needs to be assessed for Earthquake loads, as it can be used in rescue operations after earthquake events.